2015
DOI: 10.3109/13625187.2015.1057809
|View full text |Cite
|
Sign up to set email alerts
|

Factors facilitating implementation of school-based sexuality education in Portugal

Abstract: The results highlight the importance of variables at micro- and exosystem levels as facilitating factors, and reinforce the ecological approach as being well suited for SE/health education in schools. The findings have implications for policy-makers as well as for practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…By collaborating and referring out to other organizations, LEA were able to share responsibility and also ensure provision of culturallycompetent services. Therefore, inviting community agencies and organizations with similar visions of improving student health and academic outcomes to partner with local school districts is another promising approach for strengthening school-based referral systems [27].…”
Section: Discussionmentioning
confidence: 99%
“…By collaborating and referring out to other organizations, LEA were able to share responsibility and also ensure provision of culturallycompetent services. Therefore, inviting community agencies and organizations with similar visions of improving student health and academic outcomes to partner with local school districts is another promising approach for strengthening school-based referral systems [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inviting community agencies and organizations with similar visions of improving student health and academic outcomes to partner with local school districts is another promising approach for strengthening school-based referral systems. 27 Other influencing factors with the outer context domain included statewide policies, which were shown to heavily impact referral system implementation in both settings. Not only did prohibitive policies emerge as a significant barrier, we also found that having supportive statewide policies alone are not always sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It usually prepares guidelines for the implementation of sexuality education in that school, for example, in the form of a sexuality education programme (Rocha and Duarte 2015a). The likelihood of a school setting up such a programme has been found to be about 10 times higher if such a team is in place (Rocha and Duarte 2015b).…”
Section: School-based Sexuality Education In Portugalmentioning
confidence: 99%